Metode DMAIC Sebagai Solusi Pengendalian Kualitas Produksi Sepatu Tambang: Studi Kasus PT Mangul Jaya-Bekasi - Tan, Hendy Tannady (ComTech: Computer, Mathematics and Engineering Applications, 2012)
One way to increase profitability internally in PT Mangul Jaya - Bekasi is decreasing any costs produced from poor product quality by producing shoes with good quality. This study uses the DMAIC (define, measure, analyze, improve, control) method as a measuring tool. DMAIC is a quality improvement method that directly solves any problems related to the quality of a product even the primary cause of it. From the results of the study it is concluded that at the phase “define” shoes type Cheetah is the most problematic. Furthermore, on phase “measurement” it is identified that the Cp value of the Cheetah is below 1 which means that the process capability is low. After passing through the three sequencing steps (analyze, improve and control), finally this research is able to reduce the defects that occur in the shoes type Cheetah.